Pengaruh Return on Asset (ROA), Current Ratio (CR), Net Profit Margin (NPM), Debt to Equity Ratio (DER), dan Ukuran Perusahaan (SIZE) terhadap Pertumbuhan Laba pada Perusahaan Sub Sektor Makanan dan Minuman yang Terdaftar di BEI Periode 2020-2024 - Alicia Zainul; Nova Anggrainie (Eastasouth Institute, 2026)
The purpose of this study is to analyze the simultaneous, partial, andvariable effects of Return on Assets (ROA), Current Ratio (CR), NetProfit Margin (NPM), Debt to Equity Ratio (DER), and Firm Size (SIZE)on Profit Growth in food and beverage companies listed on theIndonesia Stock Exchange for the period 2020-2024. The data used inthis study is secondary data with 208 samples. The analytical tools usedin this study are Descriptive Statistics Test, Classical Assumption Test,Multiple Linear Regression Test, and Hypothesis Test. The results ofthe study indicate that ROA, CR, NPM, DER, and SIZE simultaneouslyaffect Profit Growth. Partially, ROA and DER affect Profit Growth,while CR, NPM, and SIZE do not affect Profit Growth in companies inthe food and beverage sub-sector for the period 2020-2024, and thedominant variable is DER.